Docência no ciclo II do ensino fundamental: um estudo sobre o ensino de história na rede municipal de São Paulo a partir de seus professores - Mello, Bruno Cabral de (2011)
The focus of this research was the teaching of teachers who teach the discipline of history for the first year of Cycle II of the municipal school of Sao Paulo. The main objective was to identify within the organization of teaching history, from the manifestations of this faculty, is characterized as teaching in the classroom as the educational aspects, and which aspects are related to this relationship. Through the use of questionnaires sought to determine how explicit the goals and instructional procedures used, which shape the teaching activities in the classroom, materials, and how to verify the results of his work, together with raising socio-cultural profile, their training and current professional stage. Also used were the results of the Portuguese language proficiency test for students of São Paulo region obtained during the years 2008 and 2009, besides the synthetic analysis of curricular proposals for the discipline of History, compiled by the Municipal Education for the teaching cycle. The data were obtained at different schools in the districts belonging to the Regional Board of Education of Pirituba, located in the northwest of the capital between August and November 2010. The hypothesis was that teachers are manifested superficially on matters relating to their work and their educational intentions, and present procedures that demonstrate aspects of an impoverished education. Data analysis was done by the aid of the theoretical framework of historical-cultural theory and author of Social Sciences as P. Bourdieu, J. Gimeno and M. Huberman. The data analysis identified a poor training of the student's first year of secondary school II of the evidence of proficiency in Portuguese, making it impossible, given the low level of mastery of language, the development of the various practices that teachers said conduct in the classroom. A shaky and outdated cultural and professional training of teachers, which makes use of educational jargon run within the schools found in the official proposals, coexists with considerable confusion among teachers about the distinction between procedure and teaching tasks or activities to be performed by students